2020
DOI: 10.3389/fnhum.2020.00008
|View full text |Cite
|
Sign up to set email alerts
|

Path Learning From Navigation in Aging: The Role of Cognitive Functioning and Wayfinding Inclinations

Abstract: Aging coincides with a decline in navigation and wayfinding abilities, but it is unclear to what extent factors relating to a given individual may contribute to mitigating this decline. The present study aims to analyze how older adults' objective cognitive functioning and self-reported subjective wayfinding inclinations predict their navigation performance. Sixty-four older adults were assessed on their general cognitive functioning (all scoring from 22 to 30 on the Montreal Cognitive Assessment, MoCA), visuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Indeed, higher MoCA scores related to the number of freely recalled landmarks, the canonical accuracy (categorical relations), and the distance accuracy (distance relations). These results extend the role of cognitive functioning in aging, not only after learning an environment from navigation [25,27], but also after learning a map. The role of the general cognitive level as measured with the MoCA score emerged even when the task was not as demanding, such as map drawing after map learning.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Indeed, higher MoCA scores related to the number of freely recalled landmarks, the canonical accuracy (categorical relations), and the distance accuracy (distance relations). These results extend the role of cognitive functioning in aging, not only after learning an environment from navigation [25,27], but also after learning a map. The role of the general cognitive level as measured with the MoCA score emerged even when the task was not as demanding, such as map drawing after map learning.…”
Section: Discussionsupporting
confidence: 73%
“…Some studies reported similar levels of performance in young and older adults [7,8], whereas others found impaired performance in older adults [5,6]. Concerning older adults' individual factors, we supposed that the general cognitive level as measured with the MoCA score [25,27], the visuospatial abilities, and the visuospatial wayfinding inclinations [4] could relate to spatial mental representation characteristics. The role of the subcomponents of the MoCA scores are also explored here in terms of their relationship with mental representation accuracy.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Although related to each other, these wayfinding inclinations contribute differently to route learning as a function of the spatial knowledge tested in young adults [47]. In studies adopting an adult lifespan perspective, self-reported wayfinding inclinations, such as sense of direction and pleasure in exploring, tend to remain stable throughout the adult lifespan, whereas spatial anxiety is susceptible to increasing in later life (over 70 years old; see [53,54]). Wayfinding inclinations (such as a greater sense of direction, greater pleasure in exploring places, a lower level of spatial anxiety) support environment knowledge (such as pointing cardinal points from their positions [51]) and the repetition of a route previously learned.…”
Section: The Relationship Between Individual Factors and Spatial Beha...mentioning
confidence: 99%
“…VSWM includes two different components, a passive component (visual cache) responsible for temporarily storing visual information and an active component (inner scribe) responsible for the processing and manipulation of spatial information [ 15 ]. The importance of VSWM in navigation has been extensively demonstrated [ 16 ] using different methods including real-world wayfinding [ 8 ] and focusing on healthy individuals [ 8 , 13 , 17 ], age-related changes [ 18 ], and individuals with cognitive decline [ 19 ]. Findings have consistently identified poor VSWM as responsible for unsuccessful navigation [ 20 ].…”
Section: Introductionmentioning
confidence: 99%